The Phenomena of Language Politeness in the novel entitled Lentera Mustika - Yusoff, Mohd Haniff Mohammad; Hamzani, Siti Hamira; Md. Ali, Rohaya (Idealogy Journal, 2018)
Language politeness can be defined as the ways in which language is employed in conversation with good manners and etiquette. This aspect should not only be emphasized in society, but also in novel writing. The purpose of this article is to identify and explain the politeness maxims used by the author in the novel Lentera Mustika. This language politeness seems to be very significant as novels nowadays have been the most popular genre of literature to read among Malaysians. Hence, this study will use the novel Lentera Mustika by Nisah Haron (2009) published by PTS Litera as research data. The study will also adapt Leech’s Politeness Principle (1983) for data analysis. Findings show that this novel has fulfilled the maxims of politeness proposed by Leech and portrayed that the use of good and polite language in writing can indirectly educate readers to adapt politeness in their communication. Keywords: Leech’s Politeness Principle, Language Politeness